Lack of association of ischemic heart disease with COPD when taking into account classical cardiovascular risk factors - José Luis Izquierdo (International Journal of COPD, 2010)
José Luis Izquierdo, Arturo Martínez, Elizabet Guzmán, Pilar de Lucas, José Miguel RodríguezPulmonology Department, Hospital Universitario, Guadalajara, Spain; Pulmonology Department, Hospital Gregorio Marañón, Madrid, SpainAbstract: The aim of our study is to determine whether chronic obstructive pulmonary disease (COPD) is an independent risk factor for ischemic heart disease and whether this association is related with a greater prevalence of classical cardiovascular risk factors. Ours is a case-control cross-sectional study design. Cases were hospital patients with ischemic heart disease in stable phase, compared with control hospital patients. All patients underwent post-bronchodilator (PBD) spirometry, a standardized questionnaire, and blood analysis. COPD was defined as per GOLD PBD forced expiratory volume in the first second (FEV1)/forced vital capacity (FVC) < 0.70. In our series of patient cases (n = 204) and controls (n = 100), there were 169 men in the case group (83%) and 84 in the control group (84%). Ages were 67 and 64 years, respectively (P < 0.05). There were no significant differences by weight, body mass index (BMI), pack-years, leukocytes, or homocysteine. The abdominal perimeter was significantly greater in cases (mean 101 cm ± standard deviation [SD] 10 versus 96 cm ± 11; P < 0.000). Both groups also had significant differences by C-reactive protein (CRP), fibrinogen, and hemoglobin values. In univariate analysis, increased risks for cases to show with individual classical cardiovascular risk factors were seen, with odds ratio (OR) 1.86 and 95% confidence interval (CI) (1.04–3.33) for diabetes mellitus, dyslipidemia (OR 2.10, 95% CI: 1.29–3.42), arterial hypertension (OR 2.47, 95% CI: 1.51–4.05), and increased abdominal perimeter (OR 1.71, 95% CI: 1.06–2.78). Percent predicted PBD FEV1 was 97.6% ± 23% in the patient group and 104% ± 19% in the control group (P = 0.01), but the prevalence of COPD was 24.1% in cases and 21% in controls. Therefore, COPD was not associated with ischemic heart disease: at the crude level (OR 1.19, 95% CI: 0.67–2.13) or after adjustment (OR 1.14, 95% CI:0.57–2.29). In conclusion, COPD was not associated with ischemic heart disease. The greater prevalence of classical cardiovascular risk factors in COPD patients could explain the higher occurrence of ischemic heart disease in these patients.Keywords: chronic obstructive pulmonary disease, cardiovascular disease, systemic inflammation, comorbidity